Antifouling properties of layer by layer DNA coatings. Issue 1 (2nd January 2019) - Subbiahdoss, Guruprakash; Zeng, Guanghong; Aslan, Hüsnü; Ege Friis, Jakob; Iruthayaraj, Joseph; Zelikin, Alexander N.; Meyer, Rikke Louise
Abstract: Fouling is a major concern for solid/liquid interfaces of materials used in different applications. One approach of fouling control is the use of hydrophilic polymer coatings made from poly-anions and poly-cations using the layer-by-layer (LBL) method. The authors hypothesized that the poly-anionic properties and the poly-phosphate backbone of DNA would provide anti-biofouling and anti-scaling properties. To this end, poly(ethyleneimine)/DNA LBL coatings against microbial and inorganic fouling were developed, characterized and evaluated. DNA LBL coatings reduced inorganic fouling from tap water by 90% when incubated statically or under flow conditions mimicking surfaces in heat exchangers. The coatings also impaired biofilm formation by 93% on stainless steel from tap water, and resulted in a 97% lower adhesion force and reduced initial attachment of the human pathogens Staphylococcus aureus, Staphylococcus epidermidis and Pseudomonas aeruginosa on glass. This study demonstrates a proof of concept that LBL coatings with poly-anions harboring phosphate groups can address fouling in several applications.